2004
DOI: 10.1063/1.1667251
|View full text |Cite
|
Sign up to set email alerts
|

Ceria nanoparticles: Size, size distribution, and shape

Abstract: Nanocrystalline ceria particles have been prepared by mixing aqueous solutions of cerium nitrate and hexamethylenetetramine at room temperature. The smallest size of nanoparticles synthesized is 2 nm. For each batch prepared, a narrow size distribution is found with a standard deviation less than ±15%. A transmission electron microscopy (TEM) investigation shows that these particles are single crystals having either an octahedral shape with eight {111} surfaces, or with an additional {200} surface-truncated oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
234
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(260 citation statements)
references
References 21 publications
26
234
0
Order By: Relevance
“…Wide-angle x-ray scattering (WAXS) was utilized to confirm the crystalline structure of the nanocrystals. WAXS was performed at scattering angles between 10 and 65 degrees and revealed the 5 first crystallographic orders of the fluorite structure (of symmetry Fm3 m), which is the structure of cerium oxide [14,35]. The small-angle x-ray scattering (SAXS) experiments were carried out at the Brookhaven National Laboratory on the X21 beam line at the incident wavelength 0.176 nm and sample-to-detector distance 1 meter, to cover the wave-vector range 0.008 -0.5 Å -1 .…”
Section: -Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide-angle x-ray scattering (WAXS) was utilized to confirm the crystalline structure of the nanocrystals. WAXS was performed at scattering angles between 10 and 65 degrees and revealed the 5 first crystallographic orders of the fluorite structure (of symmetry Fm3 m), which is the structure of cerium oxide [14,35]. The small-angle x-ray scattering (SAXS) experiments were carried out at the Brookhaven National Laboratory on the X21 beam line at the incident wavelength 0.176 nm and sample-to-detector distance 1 meter, to cover the wave-vector range 0.008 -0.5 Å -1 .…”
Section: -Experimentalmentioning
confidence: 99%
“…Metal oxides form a class of special interest among inorganic nanoparticles. Some primary examples are oxides of cerium [11][12][13][14][15], iron [4,5,[16][17][18][19], or zirconium [20][21][22][23][24]. Aqueous dispersions of such metal oxide particles exhibit some common properties: i) the particles have an ordered crystalline structure, ii) the sols are typically synthesized in extremely acidic (or basic) conditions, iii) the particles are stabilized by electrostatics and are extremely sensitive to perturbations in pH, ionic strength and concentration that may dramatically modify their thermodynamic stability [1,11,20,21,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…3a 30,31 , indicating that most of the copper is embedded in the host oxide forming a solid solution. In Figure 3b one can see a big increase in catalytic activity for the production of H 2 when going from 200 to 300 o C and then to 400 o C. CO 2 production followed the same curve as H 2 production and is not presented in show a line-shape typical of pure metallic copper 32,33 .…”
Section: A Wgs Reaction On Cu-ceria Nanocatalystsmentioning
confidence: 99%
“…At the same time, synthesis around room temperature has been reported by some researchers. [7][8][9] The merits of room temperature synthesis are that very small particles can be obtained because there is no aggregation of particles.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Manorama et al have synthesized nano particles of cerium oxide around room temperature by mixing hydrazine with a cerium nitrite solution and used the nano particles as the sensing material for oxygen sensors. 10 In the Manorama et al report, the sensing properties have been investigated and reported, but the detail of the room temperature synthesis of the cerium oxide nano particles was not reported.…”
Section: Introductionmentioning
confidence: 99%